Implementation of exclusive breastfeeding counseling for prospective brides in Lueng Bata District, Banda Aceh City - Agus Hendra Al Rahmad; T. Khairul Fadjri; Ampera Miko; Herry Imran; Niakurniawati Niakurniawati (Jurnal PADE: Pengabdian & Edukasi, 2022)
The importance of increasing knowledge about exclusive breastfeeding for expectant mothers in Aceh Province is an effort to achieve exclusive breastfeeding success above the national achievement of 69,7%. Optimal breastfeeding practices are one of the keys to success in reducing stunting. Counseling is essential in increasing the knowledge of prospective mothers or brides, supported by the use of media such as flyers that make it easier to understand the importance of exclusive breastfeeding for babies. This community service activity aims to increase the knowledge of prospective brides through counseling on exclusive breastfeeding using flyer media. Community service was carried out using a pretest-posttest non-equivalent group approach, namely providing exclusive breastfeeding counseling to prospective brides in Lueng Bata District. The number of participants was 20 people (10 couples), and activities were carried out in 2020. The counseling media is an exclusive breastfeeding flyer from the Indonesian Ministry of Health. Data collection was conducted through interviews using a questionnaire. The evaluation was carried out descriptively, consisting of a pretest and a posttest. The results showed an increase in average knowledge between before (26,3), and after (33,1) exclusive breastfeeding counseling was given using flyer media to prospective brides, or there was an increase in knowledge of 60,0%. In conclusion, through flyer media, exclusive breastfeeding counseling can improve the knowledge or understanding of prospective brides about exclusive breastfeeding.